Profitability of Serbian banking sector during global economic crisis - Miljković, Marko M; Filipović, Sanja; Tanasković, Svetozar (Industrija, 2013)
The aim of the paper is to identify the main factors which contributed to decline of profitability in Serbian banking sector during the period of global economic crisis. There are presented different theories of banking sector profitability and results of scientifically significant empirical researches from economic literature. Following ratios were used as measure of profitability: return on assets (ROA), return on equity (ROE), net interest gain to total revenue, net fees and commissions gain to total revenue, and net pre-tax profit/loss to total revenue ratio. The profitability was analyzed for the whole Serbian banking sector in the period 2008-2012 and particularly for the 15 largest banks according to total assets value in 2012. The empirical analysis indicated that one of the most important factors contributing to high amounts of losses of commercial banks in the previous period includes an increase of net operating expenses, especially expenses on account of a write-off of non-performing loans (NPL). Furthermore, there were analyzed the dynamics of interest rates and interest spread as a factor with certain impact on profitability of banks. Finally, it is estimated that the prospects for intensive growth of profitability in the banking sector of Serbia in the mid-term are poor.